P4 Repeat cardiac mri to determine changes in the sugen/hypoxic right ventricle with macitentan therapy. (May 2019) - Murphy, Gerard; Jayasekera, Geeshath; Mullin, James; Gallagher, Lindsay; Welsh, David
Abstract : Background: Cardiac magnetic resonance imaging (CMR) is the gold standard for assessing ventricular mass, volumes and function. Previous studies used both echocardiography and CMR to determine right ventricle (RV) response to pulmonary hypertension (PH) models, including monocrotaline and Sugen 5416 combined with chronic hypoxia (Su/Hx). They involved either a single end-stage measurement or a series of measurements taken across different rats. This study sought to use repeat CMR measurements on the same rats, providing more clinically-relevant data. Thus, enabling treated and untreated rats to be compared to their own baseline. Methods: 4 week old Sprague Dawley rats underwent an 8 week protocol, beginning with a subcutaneous injection of Sugen 5416 [20mg/kg]. This was followed by 3 weeks hypobaric hypoxic conditions (550 mmHg), then two weeks at normoxic conditions. Rats subsequently received either Macitentan (an endothelin receptor antagonist) (30 mg/kg) or vehicle (gelatin) via daily oral gavage for a further three weeks. Repeat CMR, using a Bruker Pharmascan 7T system, were taken at 5 weeks (baseline) before macitentan or the vehicle was administered, then at 7 and 8 weeks. Manual planimetry determined RV end diastolic volume (RVEDV), RV end systolic volume (RVESV), RV and LV ejection fractions (RVEF, LVEF), also RV and LV masses were also determined. Results: Treatment of Su/Hx rats with macitentan led to an improvement in RV function. This was demonstrated by an increase in RVEF from baseline through 2 and 3 weeks of treatment (32.89% vs 42.37% p<0.05 vs 48.49% p<0.05). In Su/Hx and normoxic vehicle treated rats no significant change was indicated in RVEF from baseline (39.78% vs 39.53% vs 36.35%, 57.03% vs 54.76% vs 54.79%). Macitentan treatment also reduced RV hypertrophy (RV/Left Ventricle +Septum) in Su/Hx rats across 3 weeks of treatment from an initial baseline (0.60 vs 0.47 p<0.001 vs 0.46 p<0.01). Both Su/Hx and normoxic vehicle treated rats had no significant changes in RV hypertrophy compared to their baseline (0.55 vs 0.52 vs 0.52, 0.30 vs 0.31 vs 0.29). However, comparing across the groups using only the final scan (8 week) of Su/Hx vehicle and Su/Hx macitentan treated rats demonstrated RV hypertrophy not to significantly change between Su/Hx vehicle and Su/Hx macitentan (0.52 vs 0.46). Conclusion: Using repeat CMR, we have been able to demonstrate improvements in RV function and hypertrophy. These would not be apparent if we were reliant only on end-stage measurements. The ability to measure and chart the progression of a disease and treatment from a baseline enables the replication of clinical practice in rodent models of PH.